Madagascar - Commercial agricultural promotion - World Bank (Washington, DC, 2012)
Commercial Agricultural Production (CAP) was a United States Agency for International Development (USAID)-funded technical assistance project implemented by the US development consulting firm Chemonics International between 1994 and 1999. This brief presents major achievements of CAP, benefits achieved during the project's lifetime, CAP client's evaluation of its work, and future benefits from CAP.